Incidence and risk factor of blood transfusion after abdominal radical hysterectomy for cervical cancer: a 10-year retrospective study of the US nationwide inpatient sample - Chuan Chen; BenLi Zhu; Youfeng Wang; Yangyang Zhao; Gang Chen; Ying Peng; Ying Peng; Xinyu Wang; Hao Xie; Ying Zhou; Juan Lin (BMC Cancer)
Abstract Background With the rising prevalence of abdominal radical hysterectomy, the need for perioperative blood transfusion has emerged as a significant clinical challenge. Independent risk factors for blood transfusion during abdominal radical hysterectomy remains limited, and identifying these factors is needed. Methods A retrospective analysis of data was performed using the Nationwide Inpatient Sample (NIS), focusing on patients who underwent abdominal radical hysterectomy between 2010 and 2019. Patients were categorized into two groups based on whether they received a blood transfusion. The analysis encompassed various demographic factors, including race, sex, and age, as well as length of stay (LOS), total hospitalization charges, hospital characteristics (admission type, insurance type, bed size, teaching status, geographic location, and hospital region), hospital mortality rates, comorbidities, and perioperative complications. Subsequently, both univariate and multivariate logistic regression analyses were employed to ascertain factors associated with abdominal radical hysterectomy patients requiring blood transfusions. Results Blood transfusions occurred in 14.84% of patients between 2010 and 2019, with a downward trend over time. Receiving a transfusion was associated with several negative outcomes, including a longer length of stay, higher total charges, and complications like thrombocytopenia, acute myocardial infarction, pneumonia, and so on. Additionally, patients who received transfusions were more likely to experience postoperative delirium, deep vein thrombosis, and wound infection. Independent risk factors for blood transfusion include Black race, Asian or Pacific Islander race, non-elective surgery, hospitalization in a rural setting, pre-existing medical conditions like coagulopathy, chronic blood loss anemia, deficiency anemia and others. Conversely, patients with private insurance, residing in the West, or Midwest/North Central regions were less likely to require a blood transfusion. Conclusion Our study highlights the concern of perioperative blood transfusion in radical hysterectomy, linked to significant complications. Reducing intraoperative blood loss and optimizing care based on patient factors are crucial for improving outcomes.